2005
DOI: 10.1158/1055-9965.epi-04-0570
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolites of a Tobacco-Specific Lung Carcinogen in Nonsmoking Hospitality Workers

Abstract: Exposure of nonsmokers to environmental tobacco smoke results in increased risk for cancer and other diseases. In spite of this finding, some restaurants and bars continue to permit smoking. This study examined the uptake of nicotine and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), a potent lung carcinogen, in nonsmokers who work in restaurants and bars that permitted smoking. Urine samples were collected for 24 hours on working and nonworking days and were analysed for total NNAL [the sum of 4-(methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…To convert nmol cotinine to ng, multiply by 176; for nicotine, multiply by 162. The mean level of total NNAL in the urine of these infants, 0.083 F 0.200 pmol/mL, was higher than in most other field studies involving NNK uptake from ETS (8,9,12,14). Figure 2 summarizes data from previous studies.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…To convert nmol cotinine to ng, multiply by 176; for nicotine, multiply by 162. The mean level of total NNAL in the urine of these infants, 0.083 F 0.200 pmol/mL, was higher than in most other field studies involving NNK uptake from ETS (8,9,12,14). Figure 2 summarizes data from previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have determined levels of total NNAL in the urine of newborns, children, and adults exposed to ETS (7)(8)(9)(12)(13)(14). However, there are no data in the literature on levels of total NNAL in the urine of infants (children of age V12 months) nor could we identify studies of any other carcinogen biomarker in infants exposed to ETS.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several previous studies have reported a statistically significant association between urinary NNAL and urinary cotinine (14,25,26) using data from 20 to 80 persons. Serum cotinine is often an indicator of exposure to SHS and, by inference, to the many toxicants associated with it.…”
Section: Cancer Epidemiol Biomarkers Prev; 19(11) November 2010mentioning
confidence: 99%
“…9,10 Passive exposure to cigarette smoke resulted in positive urine tests for carcinogens specific to tobacco and is associated with a higher cumulative risk of lung cancer. 11,12 The clear association between lung cancer and smoking indicates that trends in lung cancer epidemiology closely follow changes in tobacco consumption, with a lag time of 25-30 years. 13 Future trends in lung cancer will therefore be shaped by the increase in female smokers in the past few years and the higher prevalence of tobacco use in lower socioeconomic groups.…”
Section: Link To Cigarette Smokementioning
confidence: 99%